2015
DOI: 10.1016/j.jtcvs.2015.01.043
|View full text |Cite
|
Sign up to set email alerts
|

Early hemodynamic performance of the third generation St Jude Trifecta aortic prosthesis: A systematic review and meta-analysis

Abstract: The present systematic review demonstrated that short-term AVR with this prosthesis provided excellent early safety and hemodynamic outcomes with acceptable mean gradients and EOA. Long-term follow-up and randomized controlled trials are warranted to confirm the early results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 26 publications
5
18
0
Order By: Relevance
“…A mortality rate of 2.4% for isolated AVR is comparable with that reported from large volume registries [25]. In a recent systematic review and meta-analysis of 13 studies and 2549 patients receiving a Trifecta valve, the pooled 30-day mortality rate was 2.7% [14].…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…A mortality rate of 2.4% for isolated AVR is comparable with that reported from large volume registries [25]. In a recent systematic review and meta-analysis of 13 studies and 2549 patients receiving a Trifecta valve, the pooled 30-day mortality rate was 2.7% [14].…”
Section: Discussionsupporting
confidence: 67%
“…A recent systematic review and meta-analysis by Phan et al revealed that the pooled MPGs ranged from 10.7 for the Trifecta valve size 19mm to 6.0 mmHg for valve size 27 mm whereas discharge EOA ranged from 1.44 for valve size 19 to 2.50 for valve size 29 mm [14].…”
Section: Discussionmentioning
confidence: 99%
“…The reduction, however, did not reach statistical significance due to the low number of patients with severe PPM in our study. Our incidence of severe PPM calculated with LVOT D was slightly higher in comparison with the previous studies although comparable to the study of Ugur et al . A word of caution seems reasonable when the SV V method is used to diagnose PPM, because our results clearly showed increased incidence of PPM when SV V was used.…”
Section: Discussionsupporting
confidence: 89%
“…Trifecta bioprosthesis received European CE-mark approval in 2010 and Food and Drug Administration (FDA) approval in 2011 (4). Other reports have demonstrated excellent clinical results, favourable haemodynamic profile, as well as positive ventricular remodelling and mass regression (6)(7)(8)(9), but large clinical registries with longer follow-up are lacking.…”
Section: Introductionmentioning
confidence: 99%